Parents and Children: Way to Choice of Profession - G. V. Zarembo; V. V. Uglov; T. N. Gerasimenko (Научный диалог, 2017)
It is reported the monograph “Parent assistance in professional self-determination of senior pupils” (2016), prepared by T. D. Zelenkina, E. Yu. Pryazhnikova and M. G. Sergeyeva, touches upon the problem of effective vocational guidance. The value of the edition is based on the fact that problems of choosing the profession do not lose its relevance. The views of the authors of the monograph on parental involvement in career choice of their children are characterized. For example, it is noted that the family may not only contribute to the process of professional self-determination, but also prevent correct choice. Model of training parents to help in professional self-determination of senior pupils proposed by the authors is briefly described.